God's self-revelation among the agta of Isabela : a theological exploration - Sucuano II, Hilarion D. (Immaculate Conception School of Theology : [s.n.], 2020)
This study is the discussion of the self-revelation of God among the Agta of Isabela, a theological exploration. First, it aims first to discuss the Agta people of Isabela. Secondly, it aims to provide the theological grounding as why do the Agta of Isabela possess u dynamic understanding of God's self-revelation. Finally, it presents mission strategies to promote the understanding of God's self-revelation among the Agra. Since this study is contextual in nature, the "see-judge-act" method is used. It traces the life and the present situation of the Agta of Isabela and their dynamic understanding of God's self-revelation, There is a spiritual hierarchy that exists in the religious beliefs of the Agra, their attachment in particular to the created world defines not only their culture and identity but also their expression of faith. The created world becomes not only the source of their livelihood and survival but also the means to personally encounter the Divine or the Transcendence. Creation is among the principal ways of God self-manifestation. Cosmic revelation therefore is central in the dynamic understanding of God's self-revelation among the Agta of Isabela, that God continues to communicate Himself through the created world in ways known to Him alone. Education and Formation program are among the initial methods of the Local Church to promote God's self-revelation among the Agia of Isabela. The bishops, priests, lay faithful and families play a crucial role in the missionary efforts of the Church towards indigenous peoples, the Agra in particular. At one hand, they have to engage into sincere dialogue, evangelization of cultures and inculturation of the message of faith, on the other hand, cooperation and the willingness to enter into dialogue is demanded on the part of the Agta. The creation of Center for dialogue, indigenous peoples and mission serve as on- going formation in the evangelization of the Agta and in the conversion on the part of the Local Church, aiming to realize an indigenous, evangelizing and green Church.
Bibliography: pages 95-100.
CHED-La Union
Keywords: Agta -- Social and customs; Aeta -- Philippine people